Asymmetry as a Perpetual Pattern? Reconsidering Sub-Saharan Africa-China Economic Relationships - (:unkn) unknown (My University, 2024)
The economic relationships between Sub-Saharan Africa and China have intensified spectacularly since the end of the 20th century, with China becoming the region's largest trade partner. While these relationships display unique characteristics, they also share commonalities with Sub-Saharan Africa's economic ties to previous partners, particularly their asymmetry. During the first half of the 20th century, African economies were shaped by the fundamental asymmetry of the ‘open colonial economy’ model, characterized by the export of primary commodities and the import of manufactured goods from colonial powers. This asymmetry persisted after independence through the conditionalities required by international financial institutions and the inherent imbalance between creditors and debtors. China, therefore, does not appear to disrupt the asymmetric pattern of Sub-Saharan Africa's external economic relationships. It is argued that this perpetuation stems from the historically entrenched nature of this asymmetry and the poverty traps it has created within African economies.
Keywords: African Research